Can foreign aid dampen the threat of terrorism to international trade? Evidence from 78 developing countries - Simplice Asongu; Ivo J. Leke (African Governance and Development Institute (AGDI), 2018)
The study investigates whether development assistance can be used to crowd-out the negative effect of terrorism on international trade. The empirical evidence is based on a panel of 78 developing countries for the period 1984-2008 and Quantile Regressions. The following main findings are established. First, bilateral aid significantly reduces the negative effect of transnational terrorism on trade in the top quantiles of the trade distribution. Second, multilateral aid also significantly mitigates the negative effect of terrorism dynamics on trade in the top quantiles of the trade distributions. It follows that it is primarily in countries with above median levels of international trade that development assistance can be used as an effective policy tool for dampening the adverse effects of terrorism on trade. Practical implications are discussed.
Keywords: F40; F23; F35; Q34; O40; 330; Exports; Foreign Aid; Terrorism; Development